A Biocompatible Ultrananocrystalline Diamond (UNCD) Coating for a New Generation of Dental Implants - Auciello, Orlando (2022)
Implant therapy using osseointegratable titanium (Ti) dental implants has revolutionized clinical dental practice and has shown a high rate of success. However, because a metallic implant is in contact with body tissues and fluids in vivo, ions/particles can be released into the biological milieu as a result of corrosion or biotribocorrosion. Ultrananocrystalline diamond (UNCD) coatings possess a synergistic combination of mechanical, tribological, and chemical properties, which makes UNCD highly biocompatible. In addition, because the UNCD coating is made of carbon (C), a component of human DNA, cells, and molecules, it is potentially a highly biocompatible coating for medical implant devices. The aim of the present research was to evaluate tissue response to UNCD-coated titanium micro-implants using a murine model designed to evaluate biocompatibility. Non-coated (n = 10) and UNCD-coated (n = 10) orthodontic Ti micro-implants were placed in the hematopoietic bone marrow of the tibia of male Wistar rats. The animals were euthanized 30 days post implantation. The tibiae were resected, and ground histologic sections were obtained and stained with toluidine blue. Histologically, both groups showed lamellar bone tissue in contact with the implants (osseointegration). No inflammatory or multinucleated giant cells were observed. Histomorphometric evaluation showed no statistically significant differences in the percentage of BIC between groups (C: 53.40 ± 13% vs. UNCD: 58.82 ± 9%, p > 0.05). UNCD showed good biocompatibility properties. Although the percentage of BIC (osseointegration) was similar in UNCD-coated and control Ti micro-implants, the documented tribological properties of UNCD make it a superior implant coating material. Given the current surge in the use of nano-coatings, nanofilms, and nanostructured surfaces to enhance the biocompatibility of biomedical implants, the results of the present study contribute valuable data for the manufacture of UNCD coatings as a new generation of superior dental implants.